Factors associated with accepting chemotherapy despite the risk of fertility loss in Latin American breast cancer patients—LACOG 0414 study - Werutsky, Gustavo (2025)
Background: Fertility loss due to chemotherapy is a major concern for young patients with breast cancer (BC), influencing treatment decisions and quality of life. Despite established guidelines recommending fertility counseling, access to fertility preservation remains limited in Latin America. Objectives: This study evaluated attitudes and preferences regarding fertility-related concerns and chemotherapy decision-making among young Latin American women with early-stage BC. Design: A prospective cohort study was conducted at seven institutions in Brazil, Mexico, and Peru. Methods: Premenopausal women aged 18–40years with stage I–III BC requiring (neo) adjuvant chemotherapy completed a fertility questionnaire before treatment, along with validated quality-of-life assessments (EORTC QLQ-C30 and EORTC QLQ-BR23). One year after chemotherapy initiation, the patients were reassessed for ovarian function status and quality of life. Factors associated with chemotherapy acceptance despite potential infertility risks were analyzed using univariate and multivariate Poisson regression models. Results: A total of 270 patients were included (mean age, 33.9years). Prior to diagnosis, 41.5% of the women had children, and 31.1% expressed a desire for future childbearing. Among the participants, 8.5% were unaware of chemotherapy-induced infertility risks, 21.5% would decline chemotherapy if the infertility risk exceeded 25%, and 20.0% would accept treatment despite a 76%–100% infertility risk. In addition, 44.1% of patients required at least a 20% increase in survival probability to accept chemotherapy. In the multivariate analysis, married patients were significantly less likely to refuse chemotherapy (risk ratio: 0.88, 95% confidence interval: 0.82–0.94; p<0.01). One year post-treatment, 73.1% of the patients experienced chemotherapy-induced amenorrhea. Conclusion: Fertility concerns significantly impact chemotherapy decision-making in young Latin American patients with BC. Limited fertility awareness, socioeconomic disparities, and restricted access to fertility preservation contribute to these challenges. Strengthening fertility counseling and improving access to preservation options are essential for supporting informed treatment decisions in this population.